Synergetic Paradigm of Geopolitical Confrontation in the Postmodern Era - S. N. Teplyakov (Vestnik MGIMO-Universiteta)
The article analyzes current state and mechanisms of geopolitical struggle in postmodern information age that has come. The author judges from assumption that entirely new postmodern society appeared with expansion of information technology, accompanied by cardinal changes in mechanisms of political power. Information technologies have become one of the most important factors contributing to the transformation of modern society from industrial to informational (post-industrial). In modern conditions, ensuring national and global security is a comprehensive process that includes not only measures to ensure information and economic security individually, but also such an integrated component as providing both information and economic security. The author suggests that modem geopolitical confrontation is carried out based on the synergetic paradigm. The main tool is information and energy influence on enemy system weaknesses using information space control, organizing negative information campaigns and applying economic sanctions. If the main focus of geopolitical struggle in modern era was forced expansion of the territory, in information postmodern age control over economic and information space has become priority among forms of geopolitical struggle. Military expansion of modern era becomes substituted by information and economic expansionism of postmodern using synergetic paradigm of geopolitical confrontation in order to control and capture the opponent's political space.